Proyecto de inversión para la creación de una empresa que ofrezca el servicio de transporte de contenedores entre las ciudades Guayaquil y quito - Morales Apolo, Diana (2010)
This project is aimed at meeting the demand created by Importers and Exporters who require high-quality Transportation services of their cargo between the cities of Guayaquil and Quito. Recently, Ecuador has seen a substantial increase in International Trade that leads to a higher flow of goods between the previously mentioned cities. This is due to the recent changes that have been made in Customs Policies, which are expected to stay in place through out the duration of this project. Even though there exists some companies that offer a high quality service, the others are known for their informalities, lack of professionalism and poor technical development. This way we could take advantage of the market shortcomings by satisfying the requirements of our potential clients. The expected profitability of the project, based on a 10-year analysis resulted in 34.16%. The Net Present Value, considering a discount rate of 15.19%, is USD 186.879,79..